The diagnostic value of thyroglobulin in fine-needle aspiration of metastatic lymph nodes in patients with papillary thyroid cancer and its influential factors. (December 2021) - Wang, Yuxuan; Duan, Yuansheng; Zhou, Mengqian; Liu, Jin; Lai, Qingchuan; Ye, Beibei; Liu, Dandan; Li, Linqi; Fang, Yan; Yue, Kai; Jing, Chao; Wu, Yansheng; et al.
Abstract: Thyroglobulin (Tg) measurement in fine-needle aspiration (FNA-Tg) has proved to be an excellent tool to identify metastatic cervical lymph nodes (CLN) before or after surgery for papillary thyroid cancer (PTC). The diagnostic value of FNA-Tg for metastatic CLN in PTC patients is higher than that of ultrasound (US) and fine-needle aspiration cytology (FNAC), especially for small or cystic LN. The combination of FNAC and FNA-Tg can provide nearly 100% diagnostic sensitivity and specificity for CLN metastasis. However, the cutoff values of FNA-Tg for metastatic CLN have not been standardized, and the reported cutoff values of FNA-Tg range from 0.2 ng/ml to 77 ng/ml because of the differences in study samples, Tg measurement methods, Tg assays kits, etc. Serum anti-thyroglobulin antibody level, serum thyroglobulin level, the presence or absence of thyroid glands, and the characteristics of CLN may be factors affecting the accuracy of FNA-Tg. This review summarizes the recent research on the application of FNA-Tg in the diagnosis of metastatic LN in PTC and provides a reliable basis for the clinical diagnosis of cervical lymph node metastasis. Highlights: High-titer FNA-Tg strongly supports the presence of CLNM. The diagnostic value of FNA-Tg combine FNAC could reach to 100%. Each laboratory should choose its own cutoff values to suit its needs. FNA-Tg is a quantitative index, final diagnosis is based on postoperative pathology. More prospective studies should be conducted in the future.